The Clinical Implementation of Genotyping in Patients with an Acute Coronary Syndrome: Insights From the FORCE-ACS Registry - Jaouad Azzahhafi MD; Wout W. A. van den Broek MD; Dean R. P. P. Chan Pin Yin MD; Ankie M. Harmsze PharmD, PhD; Ron H. N. van Schaik MSc, PhD; Jurriën M. ten Berg MD, PhD (SAGE Publishing, 2023)
Background Guidelines recommend prasugrel or ticagrelor for acute coronary syndrome (ACS) patients. However, these P2Y 12 inhibitors increase bleeding risk compared to clopidogrel. Although genotype-guided P2Y 12 -inhibitor selection has been shown to reduce bleeding risk, data on its clinical implementation is lacking. Methods The study included ACS patients receiving genotype-guided antiplatelet therapy, utilising either a point-of-care (POC) device or laboratory-based testing. We aimed to collect qualitative and quantitative data on genotyping, eligibility for de-escalation, physician adherence to genotype results, time to de-escalation and cost reduction. Results Of the 1,530 patients included in the ACS registry from 2021 to 2023, 738 ACS patients treated with ticagrelor received a CYP2C19 genotype test. The median turnover time of genotyping was 6.3 hours (interquartile range [IQR], 3.2-16.7), with 82.3% of the genotyping results known within 24 hours after admission. POC genotyping exhibited significantly shorter turnaround times compared to laboratory-based testing (with respective medians of 5.7 vs 47.8 hours; P  < .001). Of the genotyped patients, 81.7% were eligible for de-escalation which was carried out within 24 hours in 70.9% and within 48 h in 93.0%. The time to de-escalation was significantly shorter using POC (25.4 hours) compared to laboratory-based testing (58.9 hours; P  < .001). Implementing this strategy led to a reduction of €211,150.50 in medication costs. Conclusions CYP2C19 genotype-guided-de-escalation in an all-comers ACS population is feasible. POC genotyping leads to shorter turnaround times and quicker de-escalation. Time to de-escalation from ticagrelor to clopidogrel in noncarriers was short, with high physician adherence to genotype results.